Interaction between visual and chemical cues in a Liolaemus lizard: a multimodal approach - Vicente, Natalin Soledad (2017)
Multimodal communication involves the use of signals and cues across two or more sensory modalities. The genus Liolaemus (Iguania: Liolaemidae) offers a great potential for studies on the ecology and evolution of multimodal communication, including visual and chemical signals. In this study, we analyzed the response of male and female Liolaemus pacha to chemical, visual and combined (multimodal) stimuli. Using cue-isolation tests, we registered the number of tongue flicks and headbob displays from exposure to signals in each modality. Number of tongue flicks was greater when a chemical stimulus was presented alone than in the presence of visual or multimodal stimuli. In contrast, headbob displays were fewer in number with visual and chemical stimuli alone, but significantly higher in number when combined. Female signallers triggered significantly more tongue flicks than male signallers, suggesting that chemical cues are involved in sexual recognition. We did not find an inhibition between chemical and visual cues. On the contrary, we observed a dominance of the chemical modality, because when presented with visual stimuli, lizards also responded with more tongue flicks than headbob displays. The total response produced by multimodal stimuli was similar to that of the chemical stimuli alone, possibly suggesting non-redundancy. We discuss whether the visual component of a multimodal signal could attract attention at a distance, increasing the effectiveness of transmission and reception of the information in chemical cues.